2016
DOI: 10.3109/21691401.2016.1138494
|View full text |Cite
|
Sign up to set email alerts
|

Non-ionic macroporous polystyrene adsorbents for removal of serum toxins in liver failure by hemoperfusion

Abstract: Strong base anion exchange resin (e.g., BL-300) is currently used to eliminate bilirubin from blood in clinical hemoperfusion. However, there is a potential weakness of the resin to remove heparin and activation of coagulation. To overcome this weakness, we prepared a novel non-ionic macroporous polystyrene adsorbent (SZ-9) with rich mesopores and high surface area by suspension polymerization. Test results indicated that SZ-9 performed better adsorption capacity for bilirubin than BL-300. In addition, better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Compared with CS beads, the volumes of the mesopores (2–50 nm) of AWMCNT contribute more to the total pore volume. Our previous studies showed that the specific surface area and mesopores are the key factors affecting the adsorption performance of the adsorbent for bilirubin …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with CS beads, the volumes of the mesopores (2–50 nm) of AWMCNT contribute more to the total pore volume. Our previous studies showed that the specific surface area and mesopores are the key factors affecting the adsorption performance of the adsorbent for bilirubin …”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that the specific surface area and mesopores are the key factors affecting the adsorption performance of the adsorbent for bilirubin. 21 Incorporating AMWCNT into CS could strengthen the porous structure at the same time provide a larger surface area for molecular adsorption. 9 The bilirubin adsorption tests in PBS and BSA solution both confirm the above point of view.…”
Section: Resultsmentioning
confidence: 99%
“…The HA-type resin perfusion machine used in BP belongs to macroporous resin, with the adsorption substance at a molecular weight of 500–5,000 kDa, which can adsorb many toxins that combine with protein and cell toxic substances that inhibit liver cell regeneration ( 11 ). The bilirubin adsorption column increased the capacity of bilirubin significantly ( 12 ). CVVHDF can clear medium molecular substance, blood ammonia and other toxic substances, such as false neurotransmitters, free fatty acids, mercaptan, and aromatic amino acids in patients with acute liver failure, increase the content of CAMP in cerebrospinal fluid, improve the energy metabolism in brain, and relieve and improve hepatic encephalopathy ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…A nonionic microporous poly(styrene) adsorbent, SZ-9, was also developed to avoid the activation and coagulation cascade caused by the strong basic functional groups within commercial adsorbent columns (BL-300) made from a porous anion exchange resin coated with hydrophilic 2-hydroxyethylmethacrylate copolymer. 156 Gas adsorption analysis of the SZ-9 and BL-300 adsorbents to determine the pore size distribution showed that the SZ-9 adsorbents were made up of highly porous, uniformly shaped spherical beads with a Lorentzian pore size distribution between 10 and 50 nm, and a mean value at B20 nm. However, the BL-300 adsorbents are composed of irregularly shaped but narrower pores, ranging from 1 to 10 nm, for a mean value of 3 nm.…”
Section: Sorbents For Plasma Perfusionmentioning
confidence: 99%